Ozone Inhalation Attenuated the Effects of Budesonide on Aspergillus fumigatus-Induced Airway Inflammation and Hyperreactivity in Mice - Flayer, Cameron H.; Ge, Moyar Q.; Hwang, Jin W.; Kokalari, Blerina; Redai, Imre G.; Jiang, Zhilong; Haczku, Angela (Frontiers in Immunology, 2019)
Inhaled glucocorticoids form the mainstay of asthma treatment because of their anti-inflammatory effects in the lung. Exposure to the air pollutant ozone (O3) exacerbates chronic airways disease. We and others showed that presence of the epithelial-derived surfactant protein-D (SP-D) is important in immunoprotection against inflammatory changes including those induced by O3 inhalation in the airways. SP-D synthesis requires glucocorticoids. We hypothesized here that O3 exposure impairs glucocorticoid responsiveness (including SP-D production) in allergic airway inflammation. The effects of O3 inhalation and glucocorticoid treatment were studied in a mouse model of allergic asthma induced by sensitization and challenge with Aspergillus fumigatus (Af) in vivo. The role of O3 and glucocorticoids in the regulation of SP-D expression was investigated in A549 and primary human type II alveolar epithelial cells in vitro. Budesonide inhibited airway hyperreactivity, eosinophil counts in the lung and bronchoalveolar lavage (BAL) and CCL11, IL-13, and IL-23p19 release in the BAL of mice sensitized and challenged with Af (p<0.05). The inhibitory effects of budesonide were attenuated on inflammatory changes and were completely abolished on airway hyperreactivity after O3 exposure of mice sensitized and challenged with Af. O3 stimulated the release of pro-neutrophilic mediators including CCL20 and IL-6 into the airways and impaired the inhibitory effects of budesonide on CCL11, IL-13 and IL-23. O3 also prevented the budesonide-induced release of the immunoprotective lung collectin SP-D into the airways of allergen-challenged mice. O3 had a bi-phasic direct effect with early (<12 hours) inhibition and late (>48 hours) activation of SP-D mRNA (sftpd) in vitro. Dexamethasone and budesonide induced sftpd transcription and translation in human type II alveolar epithelial cells in a glucocorticoid receptor and STAT3 (an IL-6 responsive transcription factor) dependent manner. Our study indicates that O3 exposure counteracts the effects of budesonide on airway inflammation, airway hyperreactivity and SP-D production. We speculate that impairment of SP-D expression may contribute to the acute O3-induced airway inflammation. Asthmatics exposed to high ambient O3 levels may become less responsive to glucocorticoid treatment during acute exacerbations.